Thalamic input to the lateral amygdala determines the temporal window of fear-memory association - Natália Madeira; Inês Campelo; Rosalina Fonseca (Communications Biology)
Abstract Memory consolidation is highly influenced by ongoing experiences. Here, we explore the temporal rules that determine whether events are cooperatively associated or competitively separated. We show that neutral events are associated with fearful events if they occur within less than 30 min. In some individuals, memory association can lead to a competitive suppression of the fearful response by the neutral event. Activation of the thalamic MGm inputs to the lateral amygdala, results in an increase in memory association, whereas manipulation of the cortical inputs have no effect. Introducing a third event leads to competition depending on the temporal relationship between the initial association and the competitive event. Our results show a critical temporal rule of memory association, modulated by thalamic activity that shapes fear memory consolidation.